2019
DOI: 10.1159/000503062
|View full text |Cite
|
Sign up to set email alerts
|

Tofacitinib in Pediatric Psoriasis: An Open-Label Trial to Study Its Safety and Efficacy in Children

Abstract: Introduction: Psoriasis is a chronic, multifactorial, inflammatory disorder, with an estimated prevalence of 0.71% in children. The commonly used therapeutic agents target the underlying inflammation. Tofacitinib has demonstrated efficacy in adult psoriasis. Aim: To study the efficacy, safety, and tolerability of tofacitinib in pediatric patients with moderate to severe chronic plaque psoriasis. Methods: The study included children aged between 8 and 17 years, with moderate to severe psoriasis, given tofacitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 39 publications
(46 reference statements)
0
14
0
Order By: Relevance
“…Few studies have addressed the use of oral tofacitinib in the pediatric and adolescent population for AA 9,13,14 . Craiglow et al demonstrated a low prevalence of adverse effects in adolescent patients on tofacitinib 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have addressed the use of oral tofacitinib in the pediatric and adolescent population for AA 9,13,14 . Craiglow et al demonstrated a low prevalence of adverse effects in adolescent patients on tofacitinib 9 .…”
Section: Discussionmentioning
confidence: 99%
“…At week 12, 55.32% achieved PASI 75, with 70.21% at week 36. No severe side effects were noted [107].…”
Section: Tofacitinibmentioning
confidence: 89%
“…Various cytokines released from dermal dendritic cells cause activation of T helper (Th)1 and Th17 cells, which release the cytokines causing proliferation of keratinocytes in epidermis. The activated Th1 lymphocytes secrete tumour necrosis factor‐α and IFN‐γ, while Th17 lymphocytes secrete IL‐17 24 …”
Section: Common Dermatosesmentioning
confidence: 99%